(untitled) (Brazilian Journal of Pharmaceutical Sciences, 2018)
Diacerein (DCN) was obtained by diacetylation of an anthraquinone derivative rhein and was approved by FDA in 2008, in the treatment of osteoarthritis due to its inhibitory effect on proinflammatory cytokines, including IL-6 and IL-1β. It was synthesized in 1980s and marketed as a tablet in some European Union and Asian countries from 1994. Along with its great potential in the treatment of osteoarthritis, its other applications are also being explored day by day, such as in the treatment of psoriasis, epidermolysis bullosa, breast cancer, type 2 diabetes and periodontitis. The main aim of this review is to explore mechanism of action, various applications and side effects associated with DCN. This has been reviewed that apart from the risk of diarrhea on long-term administration of DCN, various clinical studies has also shown its modest benefits in treatment of various pathological conditions. Hence, DCN is emerging as a new and potentially safe derivative with maximum therapeutic efficacies and minimum side effects which can results in improving the living status of patients suffering from various inflammatory diseases.